PERANAN LINGKUNGAN BELAJAR DALAM MENINGKATKAN MINAT BACA SISWA KELAS IV SD NEGERI 107982 - Natalina Enjela Sibarani; Umar Darwis; Sukmawati; Dara Fitrah Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The objective of the research was to determine the role of the learning environment in increasing reading interest among fourth-grade students at SD Negeri 107982 Lubuk Pakam. The research used a descriptive qualitative approach, with data collection techniques including observation, interviews, and questionnaires. The results indicate that the learning environment has a significant influence on increasing students’ reading interest. Supporting factors include comfortable classroom conditions, the availability of facilities and infrastructure such as reading corners and libraries, and the role of teachers and parents in fostering a culture of literacy. With a conducive learning environment, students are more enthusiastic about reading and show an increase in the frequency and engagement of reading activities. These findings emphasize the importance of collaboration between schools and families to create an environment that supports children’s literacy from an early age.